2011
DOI: 10.1097/mcc.0b013e328348bece
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cognitive disorders

Abstract: Purpose of review The elderly are the fastest growing segment of the population and undergo 25–30% of all surgical procedures. Postoperative cognitive problems are common in older patients following major surgery. The socioeconomic implications of these cognitive disorders are profound; cognitive decline is associated with a loss of independence, a reduction in the quality of life, and death. This review will focus on the two most common cognitive problems following surgery: postoperative delirium and postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
2
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(183 citation statements)
references
References 39 publications
3
170
2
8
Order By: Relevance
“…Whether common perioperative neurologic complications such as delirium and postoperative cognitive dysfunction are related to anesthetic neurotoxicity or other factors is similarly unknown. 37 It will be difficult to directly study the neuroprotective or neurotoxic effects of general anesthetics in patients with AIS. However, outcome studies in ischemic stroke populations are needed to define the shortterm and long-term impact of general anesthetics on the nervous system.…”
mentioning
confidence: 99%
“…Whether common perioperative neurologic complications such as delirium and postoperative cognitive dysfunction are related to anesthetic neurotoxicity or other factors is similarly unknown. 37 It will be difficult to directly study the neuroprotective or neurotoxic effects of general anesthetics in patients with AIS. However, outcome studies in ischemic stroke populations are needed to define the shortterm and long-term impact of general anesthetics on the nervous system.…”
mentioning
confidence: 99%
“…Surgical technique can affect the cognitive status of patients, and it was shown that patients with short surgical technique have lower risk to develop POCD compared to patients with long surgical technique and it is due to decreased inflammatory response [4]. In the last years it was seen that the use of anti-inflammatory strategies such as dexmedetomidine before the beginning of anesthesia, may reduce incidence of POCD [20]. Moreover, a normal nutritional status and hydration, a short period of fasting before surgery, physiological day-night rhythm, social contacts, frequent visits by family and friends aftersurgery, and early discharge from hospital are associated with reduced incidence of POCD [4].…”
Section: Resultsmentioning
confidence: 99%
“…These conditions frequently occur on the third postoperative day, which may be due to the occurrence of desaturation on the preceding night. 15,22 Additional complications arising from arterial hypoxemia may be decreased tissue oxygenation resulting in an increased risk of infection and delayed wound healing. 18,20 Finally, arterial hypoxemia results in patients attempting to compensate by increasing their respiratory rate and their effort to breathe.…”
Section: Discussionmentioning
confidence: 99%
“…This is a modification of the definition from Lewer et al 6 and Rosenberg et al 14 Demographic data, surgical procedures, site of operation, anesthetic and analgesic management, and intraoperative events were recorded. Possible risk factors for desaturation were the following: elderly 15 …”
Section: Methodsmentioning
confidence: 99%